(untitled) (Indonesian Economic Justice Review, 2024)
This paper investigates the relationship between environmental justice and economic policy in Indonesia, focusing on the impact of sustainable development initiatives on the economy. Indonesia, a resource-rich nation, faces the dual challenge of promoting economic growth while safeguarding its environment and ensuring social equity. The study explores the intersection of environmental policies, such as deforestation reduction, carbon emissions targets, and the protection of natural resources, with economic policies aimed at fostering growth in sectors such as agriculture, energy, and manufacturing. Drawing on case studies of government initiatives such as the moratorium on new palm oil plantations and the development of renewable energy projects, the paper assesses how sustainable development efforts can contribute to both environmental and economic justice. The paper argues that while sustainable development practices have the potential to create long-term economic benefits, they often conflict with short-term economic interests, particularly in industries reliant on resource extraction. The findings highlight the importance of aligning economic and environmental policies to promote a more inclusive and equitable economy, particularly for marginalized groups who are disproportionately affected by environmental degradation. The paper concludes with recommendations for strengthening environmental justice through more inclusive policymaking and the integration of sustainability into economic planning.